2010
DOI: 10.1007/s00401-010-0685-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct glutaminyl cyclase expression in Edinger–Westphal nucleus, locus coeruleus and nucleus basalis Meynert contributes to pGlu-Aβ pathology in Alzheimer’s disease

Abstract: Glutaminyl cyclase (QC) was discovered recently as the enzyme catalyzing the pyroglutamate (pGlu or pE) modification of N-terminally truncated Alzheimer’s disease (AD) Aβ peptides in vivo. This modification confers resistance to proteolysis, rapid aggregation and neurotoxicity and can be prevented by QC inhibitors in vitro and in vivo, as shown in transgenic animal models. However, in mouse brain QC is only expressed by a relatively low proportion of neurons in most neocortical and hippocampal subregions. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 74 publications
(107 reference statements)
3
39
0
Order By: Relevance
“…When N-terminal truncation exposes a glutamic acid residue, the amino terminus of Aβ can become pyrolyzed forming a stable ring [3]. One of these post-translationally modified forms of Aβ, pyrolyzed Aβ3-x (AβpE3), is abundant in brain regions affected in AD [4, 8, 9, 15, 21, 22]. A second form of pyrolyzed Aβ, Aβ11-x (AβpE11) has received less attention, but also colocalizes with Aβ1–40/42 containing plaques in AD brain [7, 12].…”
Section: Introductionmentioning
confidence: 99%
“…When N-terminal truncation exposes a glutamic acid residue, the amino terminus of Aβ can become pyrolyzed forming a stable ring [3]. One of these post-translationally modified forms of Aβ, pyrolyzed Aβ3-x (AβpE3), is abundant in brain regions affected in AD [4, 8, 9, 15, 21, 22]. A second form of pyrolyzed Aβ, Aβ11-x (AβpE11) has received less attention, but also colocalizes with Aβ1–40/42 containing plaques in AD brain [7, 12].…”
Section: Introductionmentioning
confidence: 99%
“…In double fluorescent immunolabeling procedures, secondary antibodies were Cy2-or Cy3-coupled species-specific IgGs (Dianova). Double immunofluorescent labeling of QC and A␤ was performed as described previously (Morawski et al, 2010;Hartlage-Rübsamen et al, 2011). For histological analysis and counterstaining, sections were stained with thionine or neutral red.…”
Section: Immunohistochemical and Histochemical Studiesmentioning
confidence: 99%
“…pE3-A␤ is formed enzymatically during posttranslational peptide maturation via cyclization of N-terminal glutamate residues of truncated A␤ 3-x species by glutaminyl cyclase (QC)-like enzymatic activity (Schilling et al, 2004;Cynis et al, 2008). pE3-A␤ shows a higher aggregation propensity and stability, as well as a stronger tendency to seed additional aggregation of other A␤ species (He and Barrow, 1999;D'Arrigo et al, 2009;Schlenzig et al, 2009), and QC-dependent generation of pE3-A␤ has been implicated recently in AD (Schilling et al, 2008; Morawski et al, 2010). This novel hypothesis of QC-dependent pE3-A␤-mediated neurotoxicity could explain the paradox of healthy aged individuals with high amyloid plaque load but, unfortunately, has not successfully been modeled in animals thus far.…”
Section: Introductionmentioning
confidence: 99%
“…They addressed these findings congruent to the exaggerated pupillary reaction to the cholinergic antagonist tropicamide seen in the disease. Morawski et al (2010) showed a high expression of Glutaminyl cyclase in the cholinergic nuclei of Meynert and Edinger-Westphal, related to high vulnerability of well-defined subcortical neuronal populations and their cortical projections in AD [22].…”
Section: Discussionmentioning
confidence: 99%